Efek Pemberian Ekstrak Biji Jintan Hitam (Nigella sativa) terhadap Penurunan Kadar Glukosa Darah Tikus Putih (Rattus norvegicus) yang diinduksi Streptozotocin - Evingelinda, Shania; Kurniawati, Evi; Janar Wulan, Anggraeni; Darwis, Iswandi (Medula, 2024)
Diabetes mellitus (DM) is a heterogeneous disease, characterized by chronic hyperglycemia caused by defects in insulin secretion, insulin action, or both. However, in diabetes mellitus therapy, oral hypoglycemia drugs cause side effects in form of digestive tract complaints in patients, hypoglycemia,and weight loss. Black cumin seed extract as a herbal therapy can reduce blood glucose levels. This study aims to determine effect of administering Black Cumin (Nigella sativa) extract in reducing blood glucose levels in white rats induced by streptozotocin. This study used a pre and post test control group design with a sample size of 32 white rats divided into 4 groups with treatment for 21 days. The groupK- was given 2 ml of distilled water. The group K+ was given an injection of 20 mg/kgBW streptozotocin. Thegroup P1 was given an injection of streptozotocin 20 mg/kgBW and metformin 40 mg/kgBW. Thegroup P2 was given an injection of 20 mg/kgBWstreptozotocin and 200 mg/kgBW black cuminseed extract. Assessment of blood glucose levels is carried out using a glucometer. The results of the difference in the mean pre and post test blood glucose levels at K1, K2, P1, and P2 respectively were 2,34 mg/dl, 157,4 mg/dl, 251,33 mg/dl, and 185,33 mg/dl. This study used a one-way ANOVA parametric test (p<0.05) and continued with the post-hoc Bonferroni test (p<0.05). Administration of black cumin seed extract (Nigella sativa) can have effect of reducing blood glucose levels in white rats (Rattus norvegicus) induced by streptozotocin.